2005
DOI: 10.1037/0003-066x.60.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence, race, and genetics.

Abstract: In this article, the authors argue that the overwhelming portion of the literature on intelligence, race, and genetics is based on folk taxonomies rather than scientific analysis. They suggest that because theorists of intelligence disagree as to what it is, any consideration of its relationships to other constructs must be tentative at best. They further argue that race is a social construction with no scientific definition. Thus, studies of the relationship between race and other constructs may serve social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
6

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(105 citation statements)
references
References 76 publications
0
99
0
6
Order By: Relevance
“…For example, the 2010 Census showed that the US population was 308.7 million, with 13% identified as black; however, statistics showed a far higher proportion of black individuals being convicted of crimes, with about 38% of total sentenced prisoners being black (Rastogi, Johnson, Hoeffel, & Drewery, 2011). In line with this, owing to differences in IQ across races (e.g., Herrnstein & Murray, 1994;Hunt, 2011;Rushton & Jensen, 2005;Sternberg, Grigorenko, & Kidd, 2005), the crime rates within a country might not be best reflected by the IQ distribution, particularly within the non-intellectual population. Second, it has been widely accepted that men on average have a significantly higher IQ level than women do, by a range of 3-5 points (Irwing, 2012;Irwing & Lynn, 2005;Jackson & Rushton, 2006;Keith, Reynolds, Patel, & Ridley, 2008;Lynn, 1994Lynn, , 1999Lynn & Irwing, 2004;Nyborg, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…For example, the 2010 Census showed that the US population was 308.7 million, with 13% identified as black; however, statistics showed a far higher proportion of black individuals being convicted of crimes, with about 38% of total sentenced prisoners being black (Rastogi, Johnson, Hoeffel, & Drewery, 2011). In line with this, owing to differences in IQ across races (e.g., Herrnstein & Murray, 1994;Hunt, 2011;Rushton & Jensen, 2005;Sternberg, Grigorenko, & Kidd, 2005), the crime rates within a country might not be best reflected by the IQ distribution, particularly within the non-intellectual population. Second, it has been widely accepted that men on average have a significantly higher IQ level than women do, by a range of 3-5 points (Irwing, 2012;Irwing & Lynn, 2005;Jackson & Rushton, 2006;Keith, Reynolds, Patel, & Ridley, 2008;Lynn, 1994Lynn, , 1999Lynn & Irwing, 2004;Nyborg, 2005).…”
Section: Discussionmentioning
confidence: 87%
“…Whether it is a useful venture to pursue cross-racial studies of intelligence, as races are defined by the authors, is a rather different issue. Some question whether biological races even exist (Sternberg, Grigorenko, & Kidd, 2005).…”
Section: A Concluding Commentmentioning
confidence: 99%
“…As Greenfield (1997) pointed out, only a collectivist society, such as the Maya she has studied, would view collaboration on a test as proper test-taking behavior and therefore acceptable. Indeed, intelligence is viewed differently, and manifests itself differently, in diverse cultures and other groupings (Sternberg, 2004;Sternberg, Grigorenko, & Kidd, 2005). 3.…”
Section: The Definition Of Successful Intelligencementioning
confidence: 99%